2005
DOI: 10.2114/jpa.24.333
|View full text |Cite
|
Sign up to set email alerts
|

The Hormonal Basis of Reconciliation in Humans

Abstract: Developing effective behavioral and psychological mechanisms for coping with social stress was very important in human evolution because humans evolved as social beings. The aggressive and post-aggressive behavior of 30 boys aged 7-11 years was observed during free play in summer camp with the standard "post-conflict-matched control" method (de Waal and Yoshihara, 1983). The focals were the victims of the conflict. Saliva samples for examination of cortisol and dehydroepiandrosterone sulfate levels were taken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…Plasma DHEA‐S (but not testosterone) levels were positively correlated with individual aggression ratings. Similar data have been reported in additional studies (88–90). Other research has examined children with congenital adrenal hyperplasia (CAH), who have clinically high levels of DHEA‐S.…”
Section: Neuroendocrine Control Of Aggression In Other Speciessupporting
confidence: 91%
“…Plasma DHEA‐S (but not testosterone) levels were positively correlated with individual aggression ratings. Similar data have been reported in additional studies (88–90). Other research has examined children with congenital adrenal hyperplasia (CAH), who have clinically high levels of DHEA‐S.…”
Section: Neuroendocrine Control Of Aggression In Other Speciessupporting
confidence: 91%
“…The mean level of cortisol for both conditions (n ϭ 22) at baseline was 0.31 Ϯ 0.038 g/dl and after treatment was 0.24 Ϯ 0.03 g/dl. These are consistent with the manufacturer's guidelines and within the range found in the literature (e.g., Bishop et al, 2006;Butovskaya et al, 2005;Strazdins et al, 2005;Cahill et al, 2003), providing internal validation of the method. An overall repeated measures test showed that cortisol values were significantly decreased from baseline regardless of treatment condition (F 1,7 ϭ 6.861; p Ͻ 0.05).…”
Section: Results From Data Analysissupporting
confidence: 87%
“…There are notable parallels in timing and function between reconciliation observed in young children and in non-human primates. For example, across both populations, reconciliation typically occurs in the first four minutes after a conflict [16], with the exchange often reducing the opponents' distress [15,[33][34][35][36][37]. Reconciliation is more likely to occur when opponents have an established relationship and shared social interest [38].…”
Section: Introductionmentioning
confidence: 99%